Bioactive compounds and pollen profile of honeys from northern Minas Gerais, Brazil - Veloso, Pedro Henrique Fonseca; Sacramento, Veronica de Melo; Oliveira, Dario Alves de; Menezes, Elytania Veiga; Melo Júnior, Afrânio Farias de; Souza, Luciano Fernandes de; Caldeira, Alisson Samuel Portes; Alves, Tânia Maria de Almeida; Royo, Vanessa de Andrade (Food Science and Technology, 2025)
The composition of honey is influenced by its botanical origin and geographical area. Monofloral honeys, such as those from Aroeira (Astronium urundeuva), Betônica (Hyptis sp.), Coffee (Coffea arabica), Cipó-uva (Serjania lethalis), Pequi (Caryocar brasilense), and Velame (Croton urucurana), have distinct chemical profiles that impact their sensory properties and bioactive potential. There is limited information on the chemical composition of specific monofloral honeys, and this study provides valuable data for their characterization. This study analyzed seven honey samples collected in the northern region of Minas Gerais and commercialized by Cooperativa dos Apicultores e Agricultores Familiares do Norte de Minas in 2022. The aim was to classify the honeys based on melissopalynological analysis and chemical characterization using liquid chromatography coupled with high-resolution mass spectrometry. Melissopalynological analysis identified three monofloral honeys, three with dominant flowering sources, and one multifloral honey. Chemical characterization by liquid chromatography coupled with high-resolution mass spectrometry revealed 26 bioactive compounds, including plant hormones, alkaloids, flavonoids, and coumarins. Among the identified compounds, flavonoids and coumarins are noteworthy due to their potential antioxidant and antimicrobial properties. This study expands knowledge on the chemical composition of monofloral honeys from Brazilian Cerrado species, highlighting their bioactive potential and possible pharmaceutical, nutritional, and medicinal applications.